2015
DOI: 10.4062/biomolther.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Galangin (3,5,7-Trihydroxyflavone) Shields Human Keratinocytes from Ultraviolet B-Induced Oxidative Stress

Abstract: Most skin damage caused by ultraviolet B (UVB) radiation is owing to the generation of reactive oxygen species. Phytochemicals can act as antioxidants against UVB-induced oxidative stress. This study investigated the protective effects of the flavone galangin against UVB-induced oxidative damage in human keratinocytes. Galangin efficiently scavenged free radicals and reduced UVB-induced damage to cellular macromolecules, such as DNA, lipids, and proteins. Furthermore, galangin rescued cells undergoing apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…In a previous study, we demonstrated that galangin attenuates oxidative DNA damage, lipid and protein oxidation, and expression of apoptotic proteins in human keratinocytes under UVB-induced oxidative stress (Madduma Hewage et al ., 2015). It remained unclear, however, how galangin interacts with cellular antioxidant defense mechanisms and augments cellular defenses.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous study, we demonstrated that galangin attenuates oxidative DNA damage, lipid and protein oxidation, and expression of apoptotic proteins in human keratinocytes under UVB-induced oxidative stress (Madduma Hewage et al ., 2015). It remained unclear, however, how galangin interacts with cellular antioxidant defense mechanisms and augments cellular defenses.…”
Section: Introductionmentioning
confidence: 95%
“…Galangin (3,5,7-trihydroxyflavone), a flavonoid abundant in Alpinia officinarum and Helichrysum aureonitens ( Itoh et al ., 1999 ; Ciolino and Yeh, 1999 ), has antibacterial, antiviral, and anticancer properties ( Afolayan and Meyer, 1997 ; Cushnie and Lamb, 2006 ). In a previous study, we demonstrated that galangin attenuates oxidative DNA damage, lipid and protein oxidation, and expression of apoptotic proteins in human keratinocytes under UVB-induced oxidative stress ( Madduma Hewage et al ., 2015 ). It remained unclear, however, how galangin interacts with cellular antioxidant defense mechanisms and augments cellular defenses.…”
Section: Introductionmentioning
confidence: 95%
“…UV radiation is known as the primary extrinsic factor which causes skin aging (also referred to as photoaging) because of its ability to induce oxidative stress and DNA damage (Choi et al 2015). Although the skin is equipped with a complex enzymatic and nonenzymatic defense system to maintain its intracellular redox balance, prolonged UV exposure can disrupt this system (Hewage et al 2015). Particularly, UVB can damage the epidermis and result in extremely rapid photoaging (Ichihashi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation is the primary extrinsic factor responsible for skin aging. UV radiation stimulates excessive reactive oxygen species (ROS) generation, which overwhelms cellular antioxidant defense systems and leads to oxidative stress in the skin (Hewage et al 2015;Ding et al 2015). These defense systems include protective enzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px), as well as non-enzymatic mechanisms (Piao et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] However, it also has antioxidative properties, which are attributable for its beneficial effects.…”
mentioning
confidence: 99%